Prevalence of angiostrongylus costaricensis larvae (nematoda: angiostrongylidae) in slugs vaginulus plebeius (mollusca: veronicellidae) of Costa Rica - Villalobos Charpentier, Luis (2015)
Slugs (Vaginulus plebeius) random collections were conducted during the rainiest months of the year between September 2001 and October 2007 in order to evaluate the prevalence of the parasite Angiostrongylus costaricensis in these Mollusca in their natural environment, and the risk involved for the population. Samples were taken at 50 of the 81 cantons of the country, for a total sample of 8870, finding a 3.9% infected mollusca. 48% of the cantons showed positive mollusca, San José was the province with the highest percentage of infection (5.7 %) and the lowest at Carthage 1.3%. as to the cantons Alajuelita was the city with the highest prevalence (27.4%). Finding a decrease in infection levels reported in the decades of the eighties and nineties (44%-69%), possibly due to the sampling technique and population changes over the last 25 years.